Islamic Feminism in Indonesia: The Intersection of Faith and Gender in the Modern World - Siti Aisyah; Yuliana Yuliana; Channarith Hun; Amira Jaziri (Studies in Indonesian Contemporary Religiosity and Modern World, 2025)
Islamic feminism in Indonesia has emerged as a powerful force advocating for gender equality within the context of Islamic principles. This paper examines the ways in which Indonesian Muslim women are reshaping traditional gender roles through reinterpretations of Islamic teachings. Drawing on case studies from women’s organizations, grassroots movements, and influential scholars, this paper explores how Islamic feminism in Indonesia addresses key issues such as women’s political participation, educational access, and reproductive rights. The research highlights how Indonesian Muslim women negotiate their religious identity and gender within both local and global frameworks. Through a detailed analysis of key texts and social movements, the paper contributes to the academic discourse on the intersection of faith and gender, offering new perspectives on the challenges women face in predominantly Muslim societies. By highlighting the voices and activism of Indonesian Muslim women, this research advances the understanding of how Islamic feminism can be a vehicle for social change, providing insights into how faith and modernity coexist in the pursuit of gender justice. This study contributes to the broader field of gender and religious studies by offering an in-depth look at the dynamic relationship between religion, gender, and social activism in Indonesia.